Foreign experiences in increasing the characteristics of households and the welfare of the population - Safarova Zulfizar Zafar kizi (THE INNOVATION ECONOMY, 2026)
This article analyzes the advanced experiences of the mentioned countries, examines the distinctive fea tures of households, and highlights their impact on improving population welfare. It also explores the opportunities and prospects for applying these experiences in the context of Uzbekistan.